A Questionnaire Elicitation of Surgeons’ Belief about Learning within a Surgical Trial - Cook, Jonathan A.; Ramsay, Craig R.; Carr, Andrew J.; Rees, Jonathan L. (PLOS ONE, 2012)
Introduction Surgeons gain expertise as they repeatedly conduct a procedure. Such learning is widely acknowledged to pose a challenge to evaluating new surgical procedures. Most surgical trials report little if any information on learning. We elicited surgeons’ belief regarding learning within the context of a randomised trial which assessed two surgical procedures. Materials and Methods Surgeons participating in the UKUFF trial were sent a postal questionnaire requesting details on current practice, prior experience and their belief regarding acquiring proficiency and the learning curve of operation time for two surgical procedures (open and arthroscopic rotator cuff repair). Results In total 52 (58%) participating surgeons returned a completed questionnaire. The median (IQR) number of procedures required to acquire proficiency were 17 (10,23) and 35 (23,50) for the open and arthroscopic repairs respectively. The distribution of surgeons’ belief regarding the initial point had median (IQR) of 109 (69,128) and 145 (97,171) minutes for open and arthroscopic repair respectively. Corresponding values for the plateau point were 60 (46, 82) and 79 (58, 110). Conclusions We have shown that information on the current practice, prior experience and beliefs on the learning process of a surgical procedure can be elicited using a short questionnaire. The approach could aid the interpretation of trial results in terms of generalisability and be used a priori in the design of a trial.